The Importance of Hydraulic Structures for Society: Quay Walls and Dikes in the Netherlands - Jarit de Gijt (Institute of Research and Community Outreach - Petra Christian University, 2015)
Since mankind exists, men have undertaken engineering activities to make their life more pleasant and secure. However this has not been an easy task, especially in the past. The knowledge of mathematics and physics to describe engineering problems became available only since 1400-1500. Nevertheless, great achievements have been made by man before that time, e.g. the pyramids in Egypt, the first sluice in China, the Borobudur temple in Indonesia, and the design and building activities of the Inca’s in South America. To illustrate this development, also the world economy, world ecology will be shortly mentioned. The structures that are briefly discussed in this paper are: soil and concrete dams for generating electricity, reservoirs for irrigation and drinking water, dikes, sluices, inland and sea, tunnels, and quay walls. This paper presents an overview of hydraulic structures in general with the emphasis on quay walls and dikes in the Netherlands. Examples of these structures will be discussed illustrating present state of the art and also with a view to the future. Conclusions and recommendations are given to enhance the knowledge of hydraulic structures.